Effects of Dietary Zinc Source and Level on Mammary Epithelia and Dairy Food Chemistry - J. Shaffer; K. Pandalaneni; L. Mamedova; J. DeFrain; J. Amamcharla; B. Bradford (Kansas Agricultural Experiment Station Research Reports, 2016)
Twelve lactating Holstein cows (132 ± 21 days in milk) were enrolled in a Latin square experiment to explore the extent to which source and amount of supplemental dietary Zn can impact barrier function of mammary epithelial tissue. Cows received either 970 mg supplemental Zn/day as ZnSO4(LS), 1,640 mg supplemental Zn/day as ZnSO4(HS), or 1,680 mg supplemental Zn/day as a mixture of ZnSO4and Zn methionine complex (HC). Treatments lasted for 17 days followed by 4 days of sample collection. Blood and milk were collected and analyzed for markers of blood-milk leak including plasma lactose and α-lactalbumin and milk electrolytes. Total RNA was also isolated from milk cells and abundance of Zn transporter 2 (ZnT2) and clusterin, genes with potential impact on Zn-dependent apoptosis and cell survival, were measured. Finally, dairy food properties of milk (heat coagulation time, nonprotein nitrogen, and noncasein nitrogen) were also analyzed. Cows on the HS treatment tended to have higher feed intake than LS (P = 0.06), and milk fat percentage tended to increase for HC compared to LS (P = 0.08). No other effects on milk composition, yield, or production efficiency were observed. No effects were observed on markers of blood-milk leak, mRNA abundance of ZnT2 or clusterin, or dairy food chemistry properties. Concentration and source of dietary Zn did not impact mammary epithelial integrity in lactating cows during late lactation.
Keywords: zinc; mammary epithelia; apoptosis